Streptococcus gordonii Type I Lipoteichoic Acid Contributes to Surface Protein Biogenesis - Bruno P. Lima (American Society for Microbiology, 2019)
ABSTRACT Lipoteichoic acid (LTA) is an abundant polymer of the Gram-positive bacterial cell envelope and is essential for many species. Whereas the exact function of LTA has not been elucidated, loss of LTA in some species affects hydrophobicity, biofilm formation, and cell division. Using a viable LTA-deficient strain of the human oral commensal Streptococcus gordonii, we demonstrated that LTA plays an important role in surface protein presentation. Cell wall fractions derived from the wild-type and LTA-deficient strains of S. gordonii were analyzed using label-free mass spectroscopy. Comparisons showed that the abundances of many proteins differed, including (i) SspA, SspB, and S. gordonii 0707 (SGO_0707) (biofilm formation); (ii) FtsE (cell division); (iii) Pbp1a and Pbp2a (cell wall biosynthesis and remodeling); and (iv) DegP (envelope stress response). These changes in cell surface protein presentation appear to explain our observations of altered cell envelope homeostasis, biofilm formation, and adhesion to eukaryotic cells, without affecting binding and coaggregation with other bacterial species, and provide insight into the phenotypes revealed by the loss of LTA in other species of Gram-positive bacteria. We also characterized the chemical structure of the LTA expressed by S. gordonii. Similarly to Streptococcus suis, S. gordonii produced a complex type I LTA, decorated with multiple d-alanylations and glycosylations. Hence, the S. gordonii LTA appears to orchestrate expression and presentation of cell surface-associated proteins and functions. IMPORTANCE Discovered over a half-century ago, lipoteichoic acid (LTA) is an abundant polymer found on the surface of Gram-positive bacteria. Although LTA is essential for the survival of many Gram-positive species, knowledge of how LTA contributes to bacterial physiology has remained elusive. Recently, LTA-deficient strains have been generated in some Gram-positive species, including the human oral commensal Streptococcus gordonii. The significance of our research is that we utilized an LTA-deficient strain of S. gordonii to address why LTA is physiologically important to Gram-positive bacteria. We demonstrate that in S. gordonii, LTA plays an important role in the presentation of many cell surface-associated proteins, contributing to cell envelope homeostasis, cell-to-cell interactions in biofilms, and adhesion to eukaryotic cells. These data may broadly reflect a physiological role of LTA in Gram-positive bacteria.